Eating Disorder Training and Attitudes Among Primary Care Residents. (April 2013) - Banas, David A.; Redfern, Roberta; Wanjiku, Stephen; Lazebnik, Rina; Rome, Ellen S.
Background: The ability to diagnose eating disorders (ED) is important and difficult for primary care physicians (PCPs). Previous reports suggest that PCPs feel their training is inadequate. Objective: To explore residents' interest and comfort diagnosing and treating ED. Methods: An internet survey was sent to primary care residencies. Logistic regression models were fitted to identify factors correlated with residents' interest and comfort in diagnosing and treating ED. Results: Family Medicine and Internal Medicine residents had higher interest in ED than Pediatric residents, as did female residents and residents exposed to teenagers with unexplained weight loss. Residents in programs with an ED program and faculty interested in ED were more comfortable diagnosing ED. Conclusions: Interest in, and comfort diagnosing and treating ED are associated with specialty type, presence of an ED program, presence of faculty interested in ED, and resident exposure to ED outpatients and teenagers with unexplained weight loss.